Pirmieji Vilniaus Universiteto astronomijos leidiniai - Matulaitytė, Stasė (Knygotyra, 1982)
In Lithuania the first books on astronomy were published at the press of Vilnius university and they were written by the University professors and students. In the 16-th.–17-th. centuries astronomy was taught at the University during lectures on mathematics. In those days the most distinguished professor of mathematics was Osvald Krüger (1598–1665) who founded his school of mathematics at the University. Krüger’s students, Jonas Rudamina and Albertas Diblinskis wrote and published books on astronomy, the first of the kind in the European part of the Soviet Union. J. Rudamina’s “Famous Theorems and Problems of Mathematics” (Illustriora theoremata et problemata mathematica...) published in 1633 consists of such parts as optics (44 pages), practical geometry (28 pages), and the largest part is devoted to astronomy, (it comprises astronomy, elementary sphere and a chuch calendar). The auther presents the material from the point of view of the geocentric system but refers to Copernicus’ hypothesis, makes use his data and calculations. In prisenting the theory of the movement of planets he supports Copernicus’ theory about the Earths revolving round the Sun. Diblinskis’ “Astronomic Hundred” (Centuria astronomica, 1639) is made up of a hundred guestions and answers based on Medieval astronomy. The greater part of the guestions is explained following the points of view of Aristotle’s and Ptolemy’s teachings. Diblinskis too made use of Copernicus’ works. Diblinskis’ book must have been very likely, one of the best books dealing with the fundamentals of astronomy in a popular way. The Russian translation of “Centuria astronomica”, 68 years after the publication of the books bears it out. The anonymic book “Mistakes of One Prognostic” (“Blędy jednego prognostyku”, 1654) is also merits mentioning. Having assumed the name of One Priest, the author criticises a booklet in which the people are frightened with the approaching eclipse of the Sun. To pacify the reader, the author elucidates the origin of solar eclipse, logically denies all intimidations of the forerunner. The analyses of the first University publikations on astronomy has shown them to deal with various aspects of astronomy, including the sharp movement of the planets. The axplanation of all the questions was based on the latest achievements of the world science. These publikations also had different purposes. Rudamina’s work is a scientific book presenting precise mathematical calculations and theoretical reasonings. “The Hundred” by Diblinskis and “Mistakes of one Prognostic” are popular science books. The latter is interesting because it must have been one of the first publikations concerned with exact sciences and aimed to explain the phenomena of nature to the general reader.